Selenium single-wavelength anomalous diffraction de novo phasing using an X-ray-free electron laser - Mark S. Hunter; Chun Hong Yoon; Hasan DeMirci; Raymond G. Sierra; E. Han Dao; Radman Ahmadi; Fulya Aksit; Andrew L. Aquila; Halilibrahim Ciftci; Serge Guillet; Matt J. Hayes; Thomas J. Lane; et al. (Nature Communications, 2016)
X-ray free electron lasers are increasingly available for use in macromolecular structure determination. Here, the authors describe the successful use of selenium single-wavelength anomalous diffraction data to calculate experimentally derived phases.